Síndrome uveodermatológica canina: revisão de literatura - Alves, Carlos Eduardo Fonseca [UNESP]; Amorim, Renée Laufer [UNESP]; Moura, Veridianda Maria Brianezi Dignani de (Universidade Estadual de Maringa, 2014)
Uveodermatologic syndrome is an autoimmune disorder characterized by skin lesions and uveitis that has been described in humans and dogs. The etiology is associated with autoimmune response mediated by T lymphocytes against melanocytes and melanin forming proteins are associated with the pathophysiology of the disease. When diagnosed late, can result in permanent blindness. For diagnostic purposes are considered clinical signs and histopathological findings of the skin lesions. After final diagnosis should be instituted appropriate therapeutic protocol to disease control. Among the options available include whether topical, oral or intravenous corticosteroids, cyclosporine, antimetabolites and alkylating agents administration. The prognosis of visual function depends on the time since diagnosis and initiation require systemic therapy for years. The aim of this review article is to present clinical, histopathological and therapeutic aspects of canine uveodermatologic syndrome.of immunosuppressive treatment. However, most animals lose vision due to late diagnosis. The skin lesions tend to persist and may be permanent. Some patients require systemic therapy for years, and this dependent control of owner compliance. The aim of this review article is to present clinical, histopathological and therapeutic aspects of canine uveodermatológica syndrome.

A síndrome uveodermatológica (SUD) é um distúrbio autoimune caracterizado por lesões cutâneas associadas à uveíte, sendo descrito em humanos e cães domésticos. A etiologia está relacionada à resposta autoimune mediada por linfócitos T contra melanócitos e proteínas formadoras de melanina associam-se à fisiopatologia da afecção. Quando diagnosticada tardiamente, pode resultar em cegueira permanente. Para fins diagnósticos são considerados os sinais clínicos associados aos achados histopatológicos das lesões cutâneas. Após o diagnóstico definitivo deve-se instituir protocolo terapêutico adequado para controlar a doença. Dentre as opções disponíveis destacam-se a administração tópica, oral ou intravenosa de corticosteroides, ciclosporina, antimetabólitos e agentes alquilantes. O prognóstico da função visual depende do tempo desde o diagnóstico e início do tratamento imunossupressor, no entanto, a maioria dos animais perde a visão devido ao diagnóstico tardio. As lesões dermatológicas tendem a persistir, podendo ser permanentes. Alguns pacientes necessitam de terapia sistêmica durante anos, sendo esse controle dependente da complacência do proprietário. O objetivo deste artigo de revisão é apresentar aspectos clínicos, histopatológicos e terapêuticos da síndrome uveodermatológica canina.
Canine uveodermatologic syndrome: a review
Keywords: Autoimmune disease; Dog; T lymphocyte; Melanocytes; Doença autoimune; Cães; Linfócito T; Melanócitos